Baju Lurik, Kemben dan Kemeja Perubahan Fashion Masyarakat Jelata di Surakarta Abad Ke-20 - Muhammad Misbahuddin (Proceedings of Annual Conference for Muslim Scholars, 2017)
Abstract: In the development of human civilization, especially those living in the era of the kingdom, the clothes no longer just a purely biological function, but has a social function, which is more about the culture and lifestyle of their own identity. This refers to the growing consumer culture as a result of a paradigm shift, so it makes sense to something, in other words something symbols inherent in the culture. New meanings begin to evolve as the development of clothing there, thus giving birth to the fear of the ancient cultures. Because self-existence Java community through the use and purchase of clothing is a trend at the moment. Traditional clothing in the fall of feudalism painful. Capitalization penetrated and transformed into physical symptoms and the personification of a new life among ordinary people.Keywords: Gender equity, Elementary School, gender fair education, learning environment.